Lyrics of life : Sa'di on love, cosmopolitanism and care of the self - Keshavarz, Fatemeh, 1952- (Edinburgh studies in classical Islamic history and culture., 2015)
A creative and analytical study of important facets of classical Persian poetry This imaginative and accessible study of the lyrical, humorous, social and educational aspects of classical Persian poetry focuses on the works of the master medieval poet Sa'di of Shiraz (d. 1291), one of the funniest, most influential and lyrical figures in classical Persian poetry. Sa'di, a prominent ethicist and a devout teacher of virtues, stands out for his worldliness, his practical teachings, and his love for living a wholesome life, as well as for his signature elegance and artistry that has compelled critics to call his lyrics perfectly polished diamonds. In a language deliberately free of technical jargon, Keshavarz argues for the versatility of Sa'di's poetic voice and portrays his notion of love as open to multiple perspectives including homoerotic aesthetics. She brings to life the worldly wisdom that kept the lyrical, adventurous, and ethical legacy of Sa'di fresh and effective through the passage of time. Key Features Includes hundreds of verses in translation, making it ideal for use by students Explores the connections between poetry and lived experience Highlights the role of classical Persian poetry as the 'silk road of the imagination', connecting many polities and diverse ways of life Examines the poetic strategies that give Sa'di's substantive and sumptuous lyrics their unique status